2011
DOI: 10.1177/0957650911412871
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of high-pressure turbine blade tip flows: analysis of aerodynamics

Abstract: The current contribution reports on the validation and analysis of three-dimensional computational results of the flow around four distinct high-pressure turbine blade tip geometries (TG1, 2, 3, and 4 hereinafter), taking into account the effect of the entire internal cooling setup inside the blade, at design exit Mach number: M ¼ 0.8, and high exit Reynolds number: Re C ¼ 900 000. Three of the four geometries represent different tip design solutions -TG1: full squealer rim; TG2: single squealer on the suction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Tip leakage over the flat tip blade has been described by Coull and Atkins [3]. Squealer tips featuring various wall openings were examined by Vass and Arts [4]. The authors state that the full perimeter squealer features the lowest kinetic energy losses, compared to the partial suction and pressure side squealer.…”
Section: Previous Study On Blade Tip Aerodynamicsmentioning
confidence: 99%
“…Tip leakage over the flat tip blade has been described by Coull and Atkins [3]. Squealer tips featuring various wall openings were examined by Vass and Arts [4]. The authors state that the full perimeter squealer features the lowest kinetic energy losses, compared to the partial suction and pressure side squealer.…”
Section: Previous Study On Blade Tip Aerodynamicsmentioning
confidence: 99%
“…They found that the strength of tip leakage flow and total pressure loss in cascade are increased with the increase of tip gap size. Vass and Arts 31 numerically computed the pressure distributions and leakage flow structures in a worn squealer tipped blade. They revealed that the kinetic loss rises remarkably in worn case compared to the original design case.…”
Section: Introductionmentioning
confidence: 99%
“…Key and Arts [8] compared flat tips and squealer tips and Vass and Arts [9] investigated different squealer designs with and without openings. Both partial and full perimeter squealers were found to operate like labyrinth seals where each squealer rim causes additional flow separation, blocking the leakage flow [10].…”
Section: Introductionmentioning
confidence: 99%